Alteration of ceruloplasmin in patients with malaria: a systematic review and meta-analysis of observational studies - Kwuntida Uthaisar Kotepui; Aongart Mahittikorn; Polrat Wilairatana; Frederick Ramirez Masangkay; Manas Kotepui (Malaria Journal)
Abstract Background The evidences of oxidative stress-related Plasmodium infection may alter the ceruloplasmin levels were inconsistent. This systematic review and meta-analysis aimed to collate and synthesize literatures on malaria and ceruloplasmin concentrations. Methods The systematic review has been registered with PROSPERO (CRD42023454859). Six electronic databases were systematically searched for investigated ceruloplasmin levels in malaria: ProQuest, EMBASE, MEDLINE, Ovid, PubMed, and Scopus, from their inception to August 2023. The quality of the included studies was assessed using the Joanna Briggs Institute (JBI) critical appraisal tools for cross-sectional, cohort, and case–control studies. Qualitative synthesis was undertaken to summarize findings from the included studies. For quantitative synthesis, a meta-analysis was performed using random-effects models. Results A total of 411 articles were retrieved, and nine studies were included in the review. The majority of included studies found significantly increased ceruloplasmin levels in malaria patients compared to uninfected controls. The meta-analysis showed a significant increase of ceruloplasmin in patients with malaria as compared to uninfected controls (P < 0.01, Hedge’s g 1.18, 95% CI 0.90–1.47, I 2  59.19%, eight studies). Conclusion The systematic review and meta-analysis consistently revealed a significant rise in ceruloplasmin levels among malaria patients. Further research is essential to understand the variations in ceruloplasmin levels between different Plasmodium species and the severity of malaria in patients.